Caracterização molecular e análise filogenética de rotavírus a em população infantil com e sem diarreia no semiárido brasileiro. - Pankov, Rafaela Chemello (2017)
Rotavirus A (RVA) is the major cause of infantile acute gastroenteritis, being responsible for approximately 40% of all diarrhea cases in children younger than 5 years of age worldwide. After the Rotarix vaccine (RV1) introduction in Brazil, the rates of childhood gastroenteritis-related deaths decreased, however, morbidity rates are still high. This study aimedto investigate the epidemiology, clinical features, vaccination impact and genetic diversity of circulating RVA strains associated with acute gastroenteritis, in children from Semiarid region in northeastern Brazil. As part of the Recodisaproject was included 1200 children in the age group 2-36 months, whereas cases were children with an episode of diarrhea in the last 14 days, and was recruited participants from the cities of Crato (CE), Picos (PI), Ouricuri (PE), Cajazeiras (PB), Souza (PB) and Patos (PB) during the years 2009 to 2011. The initial clinical diagnosis showed RVA prevalence of 7.1% (86/1200) using Luminex. Subsequently, 291 samples were selected for analysis by real-time PCR (qRT-PCR), to detection of the gene coding for VP6 and sequence analyses of the genes encoding VP4 and VP7. By using qRT-PCR, the detection rate of RVA was 10.65% positive, which was associated with infantile diarrhea (P = 0.0472). In addition,RVA infections was related to the male gender (P = 0.0216). The absence of RVA was associated with the first one (P = 0.0001) and the third year of life (P = 0.0190), corroborating with the vaccination rates, where 89,3% of the children in the study received the two doses of the vaccine. Exclusive breastfeeding was also associated with the absence of RVA (P = 0.0012). The majority of children with RVA were observed slightly reduced symptoms of acute gastroenteritis and 80.7% presented a good nutritional status. The genotypes G1, G2 and G3 and P[4], P[8] and P[9] were detected, and the most prevalent combination was G1P[8] (57%). Rare combinations were also detected, such as G1P[4], G2P[8] and G3P[9]. The phylogenetic analysis of the strains shows that the genotype samples as P[8] belong to the lineage P[8]-1, this is the same lineage of RV1 and have nucleotide similarity ranging from 98 to 100%. It is suggested that samples G1 and P[8] show evidence of vaccine shedding. Thus, the vaccine’s virus excreted into the environment, is linked to direct protection of unvaccinated children, consequently the effect of herd immunity provides a measure of protection for populations with low vaccine coverage. In conclusion, this study observed that after the introduction of RV1 and other preventive measures, there was a reduction in cases of RVA, besides the results contribute to the understanding of the genetic diversity of RVA in children from Semiarid region in northeastern Brazil.